Filsafat Hukum Kesehatan: Antara Hak atas Kesehatan, Keadilan Sosial dan Tanggung Jawab Negara di Era Universal Health Coverage (UHC) - Aka Al Fahrezir (Himpunan Ilmu Hukum dan Ilmu Hukum Islam, 2025)
The philosophy of health law plays a pivotal role in guaranteeing the right to health, social justice and state responsibility for equitable services. This right is grounded in the Universal Declaration of Human Rights and the International Covenant on Economic, Social and Cultural Rights; however, its implementation in Indonesia still faces social, economic and geographical disparities. Universal Health Coverage programs, such as the National Health Insurance (JKN), are expected to expand access, although the distribution of services remains uneven. This research analyzes the role of the philosophy of health law in formulating solutions that are equitable, inclusive and oriented toward human rights.